Biodiesel Production Using Waste Cooking Oil Energy Optimization Study Using Pinch And Heat Exchanger Network HEN Analysis - Yaacob, Jeredraj (Universiti Sains Malaysia, 2022)
In this work, an integrated process for production of biodiesel using WCO was done by constructing the ideal heat exchanger network (HEN) and conducting an energy optimization study utilising pinch analysis. The heating and cooling energy necessary for all process streams was integrated using pinch technology. In this research, it is assumed that Tmin = 10°C. Heat composite curve was used to identify the pinch temperatures. The pinch temperature, minimum heating and cooling energy requirements, and drawing of the composite curve were all obtained using the Aspen Energy Analyzer software. The temperatures at which the pinch occurs are 177°C, 165°C, 125°C, 115°C, 50°C, and 40°C. For this process, the minimum hot utility (Qhmin) is 10,411,031 kJ/hr, while the minimum cold utility (Qcmin) is 7,967,105.73 kJ/hr. New HENs were designed using the AEA-recommended design, and comparisons between all the design cases and the base case were made in order to decrease process energy consumption and improve energy integration between process streams. Because it is more energy and economically efficient than the other two cases, design case 2 has been chosen as the best HEN. Comparison of design case 2 with base case indicates massive energy and cost saving potential where 3,203,188.31Watt of hot utility energy and 3,306,114.41 Watt of cold utility energy can be saved. The estimation of energy cost saving will be around USD 295,146 per year for hot utility and USD 23,808 per year for cold utility.